Insuficiencia jurídica en el código de trabajo en cuanto a la prescripción de las acciones provenientes de los actos o contratos de trabajo. - Macas Espinoza, Elsa Natali (2014)
The article 33 of the Constitution of the Republic of the Ecuador, establishes that "work is a right and a social duty, and an economic right, source of personal realization and base of the economy." The State will guarantee workers full respect to their dignity, a decent life, pay and fair remuneration and the performance of healthy and freely chosen or accepted work".3 The Constitution of the Republic has expressly, that worker rights are inalienable. Any provision that involves his resignation, decrease or alteration shall be null. And he says more. That the State shall guarantee the inviolability of those rights. With this express regulations of the fundamental norm, is clearly observed the legal inconsistency expressed in the labour code to determine the prescription of acts or contracts of employment from legal action. It is to say that the labour code in its article 635 establishes that "from actions of the acts and contracts of employment prescribed in three years from the termination of the employment relationship, without prejudice to the provisions in the articles that follow, and in other cases of limitation of short time, particularly referred to in this code".4 Which, is not effectively guaranteed the inalienable right of the worker, since that should not have prescription action claim or demand by any act or labour contract. 3 CONSTITUTION OF THE REPUBLIC OF ECUADOR; Corporación de Estudios y Publicaciones; 2014. 4 CODE OF LABOUR OF ECUADOR; Corporación de Estudios y Publicaciones; 2014. Hence the imperative need for scientific research, to identify and remedy the legal gap in the labour code, because it causes serious transgressions of the Ecuadorian worker rights.